2022
DOI: 10.3390/rs14030475
|View full text |Cite
|
Sign up to set email alerts
|

Grassland Phenology Response to Climate Conditions in Biobio, Chile from 2001 to 2020

Abstract: Plant phenology is affected by climate conditions and therefore provides a sensitive indicator to changes in climate. Studying the evolution and change in plant phenology aids in a better understanding of and predicting changes in ecosystems. Vegetation Indices (VIs) have been recognized for their utility in indicating vegetation activity. Understanding climatic variables and their relationship to VI support the knowledge base of how ecosystems are changing under a new climatic scenario. This study evaluates g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Some studies have reported that rising temperatures could cause the growth season in cold regions to advance [9,10], while others have reported delays in the growing season in warm regions [11,12]. Plants in regions with higher latitudes exhibit greater sensitivity to alterations in temperature compared to those located at mid or low latitudes [13][14][15][16]. Moreover, SOS has different temperature requirements for different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that rising temperatures could cause the growth season in cold regions to advance [9,10], while others have reported delays in the growing season in warm regions [11,12]. Plants in regions with higher latitudes exhibit greater sensitivity to alterations in temperature compared to those located at mid or low latitudes [13][14][15][16]. Moreover, SOS has different temperature requirements for different seasons.…”
Section: Introductionmentioning
confidence: 99%
“…After applying the Savitzky-Golay filter [52] in TIMESAT, a seasonality parameter per year was chosen, representing a phenological cycle with a start and end level of 20% of the seasonal amplitude. This threshold value was used in several studies and is known to be accurate in registering the plant's phenological transitions [53][54][55][56][57][58]. The four phenological metrics are shown in boxplot graphics for each ecoregion studied and used for correlations with environmental drivers.…”
Section: Phenological Metricsmentioning
confidence: 99%
“…Firstly, it is labor- and time-intensive, necessitating both fixed-point and species-specific observations. Secondly, the coverage of ground observation sites is often restricted [ 10 ], particularly in challenging environments such as alpine tundra and arid deserts [ 11 ]. Finally, the lack of a standardized protocol for ground observations leads to variations in phenological definitions among observers, thus impeding data exchange and harmonization.…”
Section: Introductionmentioning
confidence: 99%